Mitogen-Activated Protein Kinase 14 Promotes AKI - Ortiz, Alberto (J Am Soc Nephrol, 2017)
An improved understanding of pathogenic pathways in AKI may identify novel therapeutic approaches. Previously, we conducted unbiased liquid chromatography-tandem mass spectrometry–based protein expression profiling of the renal proteome in mice with acute folate nephropathy. Here, analysis of the dataset identified enrichment of pathways involving NFκB in the kidney cortex, and a targeted data mining approach identified components of the noncanonical NFκB pathway, including the upstream kinase mitogen-activated protein kinase kinase kinase 14 (MAP3K14), the NFκB DNA binding heterodimer RelB/NFκB2, and proteins involved in NFκB2 p100 ubiquitination and proteasomal processing to p52, as upregulated. Immunohistochemistry localized MAP3K14 expression to tubular cells in acute folate nephropathy and human AKI. In vivo, kidney expression levels of NFκB2 p100 and p52 increased rapidly after folic acid injection, as did DNA binding of RelB and NFκB2, detected in nuclei isolated from the kidneys. Compared with wild-type mice, MAP3K14 activity–deficient aly/aly (MAP3K14(aly/aly)) mice had less kidney dysfunction, inflammation, and apoptosis in acute folate nephropathy and less kidney dysfunction and a lower mortality rate in cisplatin-induced AKI. The exchange of bone marrow between wild-type and MAP3K14(aly/aly) mice did not affect the survival rate of either group after folic acid injection. In cultured tubular cells, MAP3K14 small interfering RNA targeting decreased inflammation and cell death. Additionally, cell culture and in vivo studies identified the chemokines MCP-1, RANTES, and CXCL10 as MAP3K14 targets in tubular cells. In conclusion, MAP3K14 promotes kidney injury through promotion of inflammation and cell death and is a promising novel therapeutic target.